Chitosan-zinc oxide-acrylate composite material, preparation method and application thereof
By polymerizing modified chitosan-zinc oxide with acrylate monomer, a chitosan-zinc oxide-acrylate composite material with water resistance, antibacterial and good biocompatibility was prepared, which solved the shortcomings of existing antibacterial materials in water resistance, biocompatibility and antibacterial effects, and achieved effective prevention of bacterial infection and promotion of cell activity.
Patent Information
- Application Number
- CN202211657405.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-22
AI Technical Summary
Existing antibacterial materials have shortcomings in water resistance, biocompatibility and antibacterial effects, and it is difficult to effectively prevent bacterial infection in the long term.
Modified chitosan-zinc oxide and acrylate monomer were used for polymerization to prepare chitosan-zinc oxide-acrylate composite materials with water resistance, antibacterial and good biocompatibility.
The water resistance of composite materials in wound dressings is improved, antibacterial performance enhancement and biocompatibility improvement, which can effectively prevent bacterial infection and promote cell activity.
Smart Images

Figure CN115960313B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antibacterial materials, and in particular to a chitosan-zinc oxide-acrylate composite material, a preparation method and application thereof. Background Art
[0002] In recent years, infections caused by bacteria and other microorganisms are the main cause of death every year around the world. Antibiotics, as a traditional antibacterial agent, have been widely used in the past. However, excessive use of antibiotics can also cause a series of problems, such as the evolution of drug-resistant strains. For such problems, some commonly used methods are to adjust the formulation and dosage of multiple antibiotics to solve the drug resistance of bacteria and microorganisms in the short term, or to simply prevent bacteria and microorganisms from adhering to prevent their proliferation on different substrate surfaces. However, these methods cannot provide long-term and effective solutions to infections caused by the proliferation of bacteria and microorganisms. Therefore, the research and development of new antibacterial materials is becoming an excellent way.
[0003] Antibacterial materials that prevent bacterial infection and reduce bacterial toxicity have attracted great interest from relevant researchers. Although traditional wound dressings can prevent bacterial growth to a certain extent, they have the disadvantages of poor water resistance, poor biocompatibility, and poor antibacterial effect. Therefore, the preparation of a wound dressing with good water resistance, antibacterial and biocompatibility is a technical problem that needs to be solved urgently.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a chitosan-zinc oxide-acrylate composite material, a preparation method and application thereof, aiming to prepare a composite material having water-resistant and antibacterial effects and good biocompatibility.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a chitosan-zinc oxide-acrylate composite material, which is obtained by polymerizing modified chitosan-zinc oxide and acrylate monomers, and the modifier used in the preparation process of the modified chitosan-zinc oxide is a silane compound.
[0008] In an optional embodiment, the molar ratio of chitosan to zinc oxide is 1:0.5-1.5, the mass ratio of chitosan-zinc oxide to modifier is 100:1-40, and the mass ratio of modified chitosan-zinc oxide to acrylate monomer is 0.5-15:100;
[0009] Preferably, the molar ratio of chitosan to zinc oxide is 1:0.8-1.2, the mass ratio of chitosan-zinc oxide to modifier is 100:5-25, and the mass ratio of modified chitosan-zinc oxide to acrylate monomer is 3-10:100;
[0010] Preferably, the modifier is selected from at least one of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.
[0011] In a second aspect, the present invention provides a method for preparing the chitosan-zinc oxide-acrylate composite material in the aforementioned embodiment, comprising: preparing modified chitosan-zinc oxide, and then polymerizing the modified chitosan-zinc oxide with an acrylate monomer.
[0012] In an optional embodiment, the preparation process of modified chitosan-zinc oxide includes: mixing chitosan-zinc oxide powder with a first solvent and a modifier, and reacting at 50° C. to 100° C. for 1 h to 8 h;
[0013] Preferably, the first solvent is selected from at least one of methanol, ethanol, water and isopropanol;
[0014] Preferably, after the reaction with the modifier is completed, solid-liquid separation, washing and drying are carried out in sequence.
[0015] In an optional embodiment, the preparation process of chitosan-zinc oxide powder includes: mixing chitosan and a zinc source in an acidic solution, then adjusting the pH value to 8 to 11 with an alkaline solution, and reacting at 60° C. to 100° C. for 2 h to 6 h to obtain a suspension;
[0016] Preferably, the chitosan is first mixed with the acidic solution and then mixed with the zinc source;
[0017] Preferably, the method further comprises: sequentially subjecting the suspension to solid-liquid separation, washing and drying.
[0018] In an optional embodiment, the zinc source is selected from at least one of zinc acetate dihydrate and zinc nitrate hexahydrate;
[0019] Preferably, the acidic solution is selected from at least one of an acetic acid solution and an oxalic acid solution;
[0020] Preferably, the alkali solution is selected from at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkali solution is 1 mol / L to 5 mol / L.
[0021] In an optional embodiment, the process of polymerizing the modified chitosan-zinc oxide and the acrylate monomer comprises: mixing the modified chitosan-zinc oxide, the acrylate monomer and the second solvent, and performing a polymerization reaction in the presence of an initiator;
[0022] Preferably, the polymerization reaction temperature is 40°C to 100°C, and the polymerization reaction time is 2h to 10h;
[0023] Preferably, the method further comprises: washing and drying after the polymerization reaction is completed; more preferably, the washing is performed multiple times using water and an alcohol solvent respectively.
[0024] In an optional embodiment, the mass ratio of modified chitosan-zinc oxide to acrylate monomer is 0.5-15:100;
[0025] Preferably, the second solvent is selected from at least one of cyclohexane, isooctane and toluene;
[0026] Preferably, the initiator is selected from at least one of benzoyl peroxide and azobisisobutylnitrile, and the mass ratio of the initiator to the acrylate monomer is 0.1 to 2:100.
[0027] In an optional embodiment, the acrylate monomer is selected from at least one of methyl methacrylate, lauryl methacrylate, butyl acrylate and isooctyl acrylate;
[0028] Preferably, the acrylate monomer includes a soft acrylate monomer and a hard acrylate monomer, and the mass ratio of the soft acrylate monomer to the hard acrylate monomer is 1:1.7 to 4.5; the soft acrylate monomer is selected from at least one of lauryl methacrylate, butyl acrylate and isooctyl acrylate, and the hard acrylate monomer is selected from at least one of methyl methacrylate, methyl acrylate and isobornyl acrylate.
[0029] In a third aspect, the present invention provides a chitosan-zinc oxide-acrylate composite material according to any one of the aforementioned embodiments or a chitosan-zinc oxide-acrylate composite material prepared by the preparation method according to any one of the aforementioned embodiments in preparing a wound dressing;
[0030] Preferably, the preparation process of the wound dressing comprises: mixing the chitosan-zinc oxide-acrylate composite material with a dressing solvent.
[0031] The present invention has the following beneficial effects: by using silane compounds as modifiers to modify chitosan-zinc oxide to obtain modified chitosan-zinc oxide, and by polymerizing the modified chitosan-zinc oxide with acrylate monomers, a composite material having water resistance, antibacterial properties and good biocompatibility can be obtained. The chitosan-zinc oxide is a hybrid particle with a higher antibacterial effect obtained by depositing zinc oxide on the macromolecular chain of chitosan using the chelation mechanism of chitosan, and the acrylate is an excellent polymer substrate. The composite material can be used as a wound dressing and can form a water-resistant and antibacterial film on the wound surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 The results of the water resistance test, 1 to 6 in the figure respectively show the dissolution of the blue pigment of the wound dressing of Examples 1-5 and Comparative Example 1 over time;
[0034] Table 1 and Figure 2 The results of the antibacterial performance test, in which the control group in the figure represents the antibacterial effect of the polyacrylate wound dressing on Escherichia coli for 24 hours, and 1 to 8 in the figure represent the antibacterial effect of Examples 1-5 and Comparative Examples 1-3 on Escherichia coli for 24 hours respectively;
[0035] Figure 3 Figures 1 to 6 are biocompatibility test results of live and dead cells staining of Examples 1-5 and Comparative Example 1, respectively;
[0036] Figure 4 is a graph showing the results of a biocompatibility test, in which 1 to 6 are the CCK8 test results of Examples 1-5 and Comparative Example 1, respectively;
[0037] Figure 5 1 to 6 are the water vapor transmission rate test results of Examples 1-5 and Comparative Example 1, respectively. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] The embodiment of the present invention provides a method for preparing a chitosan-zinc oxide-acrylate composite material, comprising the following steps:
[0040] S1. Preparation of chitosan-zinc oxide powder
[0041] The preparation process of chitosan-zinc oxide powder includes: mixing chitosan and zinc source in an acidic solution, then adjusting the pH value to 8-11 with alkaline solution, reacting at 60℃-100℃ for 2h-6h to obtain a suspension; and sequentially performing solid-liquid separation, washing and drying on the suspension to obtain chitosan-zinc oxide powder. Zinc ions in the zinc source are precipitated under alkaline conditions, and zinc oxide is obtained after drying. The adsorption effect of the groups on the surface of chitosan is used to make the uniformity of chitosan and zinc oxide in the final chitosan-zinc oxide mixed powder higher.
[0042] It should be noted that zinc oxide is a functional antibacterial active substance and exhibits excellent affinity for skin tissue. Zinc oxide composite modified polymers can bring many improvements to the properties of polymers, such as antibacterial properties, mechanical properties, optical properties, etc. Chitosan has special biodegradability, immunoactivity and antibacterial properties due to its unique chemical structure. At the same time, as a natural polymer, it also has good biocompatibility, cell non-toxicity, tissue repair and other characteristics. The prepared chitosan-zinc oxide has excellent antibacterial properties.
[0043] Specifically, the pH value is adjusted to 8 to 11 with alkaline solution, and it can be within this range. The reaction temperature can be 60°C, 70°C, 80°C, 90°C, 100°C, etc., and the reaction time can be 2h, 3h, 4h, 5h, 6h, etc. After the reaction is completed, the means of solid-liquid separation are not limited, and centrifugal separation and other means can be used. The separated solid is washed to remove unreacted impurities, and the washing can be water washing, and the number of water washings is not limited to 1-3 times. The washed precipitate can be dried in a vacuum drying oven, and the drying temperature is not limited, such as 60°C-80°C.
[0044] In some embodiments, chitosan is first mixed with an acidic solution and stirred for 10 to 30 minutes, and then mixed with a zinc source and stirred for 15 to 30 minutes to ensure uniformity of the raw material mixture. The molar ratio of chitosan to zinc oxide is 1:0.5 to 1.5 (such as 1:0.5, 1:1.0, 1:1.5, etc.) to ensure the antibacterial properties of the composite material.
[0045] In some embodiments, the zinc source is selected from at least one of zinc acetate dihydrate and zinc nitrate hexahydrate, and the zinc source can be selected from any one or more of the above. The acidic solution is selected from at least one of acetic acid solution and oxalic acid solution, and can be selected from any one or more of the above acidic aqueous solutions. The alkali solution is selected from at least one of sodium hydroxide solution and potassium hydroxide solution, and can be one or more, and the concentration of the alkali solution is 1mol / L to 5mol / L, such as 1mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, etc.
[0046] S2. Preparation of modified chitosan-zinc oxide
[0047] The composite powder obtained in S1 is modified by using silane compounds to increase its dispersibility in organic solvents, and reactive double bonds are introduced to prepare modified chitosan-zinc oxide with carbon-carbon double bonds, which participates in the reaction and copolymerizes in the subsequent polymerization.
[0048] In some embodiments, the modifier is selected from at least one of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane, and can be any one or more of the above. The mass ratio of chitosan-zinc oxide to the modifier is 100:1-40, preferably 100:5-20, such as 100:1, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, etc.
[0049] In actual operation, the preparation process of modified chitosan-zinc oxide includes: mixing chitosan-zinc oxide powder with the first solvent and the modifier, and reacting for 1 hour to 8 hours at 50°C to 100°C to fully react. Specifically, the reaction temperature can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc., and the reaction time can be 1 hour, 3 hours, 5 hours, 8 hours, etc.
[0050] In some embodiments, the first solvent is selected from at least one of methanol, ethanol, water and isopropanol, and can be any one or more of the above.
[0051] In some embodiments, after the reaction with the modifier is completed, a white suspension is obtained, and then solid-liquid separation, washing and drying are carried out in sequence. The means of solid-liquid separation are not limited, and centrifugal separation and other means can be used. The separated solid is washed to remove unreacted impurities, and the washing can be water washing, and the number of water washings is not limited to 1-3 times. The washed precipitate can be dried in a vacuum drying oven, and the drying temperature is not limited, such as 60°C-80°C.
[0052] S3, in-situ polymerization
[0053] The modified chitosan-zinc oxide is polymerized with acrylate monomers. The acrylate polymer is an excellent base material and is suitable for the preparation of the wound dressing in the embodiment of the present invention.
[0054] In the actual operation process, the process of polymerizing the modified chitosan-zinc oxide and the acrylate monomer includes: mixing the modified chitosan-zinc oxide, the acrylate monomer and the second solvent, carrying out a polymerization reaction in the presence of an initiator, controlling the polymerization reaction temperature to 40°C to 100°C, and the polymerization reaction time to 2h to 10h to allow the reaction to proceed fully.
[0055] Specifically, the polymerization side reaction temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc., and the reaction time can be 2h, 5h, 8h, 10h, etc.
[0056] In some embodiments, the mass ratio of modified chitosan-zinc oxide to acrylate monomer is 0.5-15:100; the acrylate monomer is selected from at least one of methyl methacrylate, lauryl methacrylate, butyl acrylate and isooctyl acrylate, and may be any one or more of the above.
[0057] In some embodiments, the acrylate monomer includes a soft acrylate monomer and a hard acrylate monomer, and the mass ratio of the soft acrylate monomer to the hard acrylate monomer is 1:1.7 to 4.5 (such as 1:1.7, 1:2.0, 1:2.5, 1:3.0, 1:3.5, 1:4.0, 1:4.5, etc.); the soft acrylate monomer is selected from at least one of lauryl methacrylate, butyl acrylate, and isooctyl acrylate, and the hard acrylate monomer is selected from at least one of methyl methacrylate, methyl acrylate, and isobornyl acrylate. The combination of soft monomers and hard monomers is conducive to making the resulting composite material have sufficient cohesion and strength while having a certain degree of adhesion.
[0058] In some embodiments, the second solvent is selected from at least one of cyclohexane, isooctane and toluene, and can be any one or more of the above. The amount of the solvent is not limited, as long as it can dissolve or disperse the raw materials well. The initiator is selected from at least one of benzoyl peroxide and azobisisobutyronitrile, and can be any one or more of the above. The mass ratio of the initiator to the mass ratio of the acrylate monomer is 0.1 to 2:100, such as 0.1:100, 0.5:100, 1.0:100, 1.5:100, 2.0:100, etc.
[0059] In some embodiments, washing and drying are performed after the polymerization reaction is completed. After the polymerization is completed, a viscous oily substance is obtained, which can be repeatedly washed 1-3 times with water and an alcohol solvent (such as ethanol) to obtain a white viscous substance. The viscous substance is placed in a vacuum drying oven and dried to obtain a zinc oxide-acrylate composite material with water-resistant and antibacterial properties.
[0060] The embodiment of the present invention also provides a chitosan-zinc oxide-acrylate composite material, which is obtained by polymerizing modified chitosan-zinc oxide and acrylate monomers. The modifier used in the preparation process of the modified chitosan-zinc oxide is a silane compound. The chitosan-zinc oxide-acrylate composite material has the advantages of water resistance, antibacterial properties, good biocompatibility, etc., and can be used as a wound dressing.
[0061] In some embodiments, the molar ratio of chitosan to zinc oxide is 1:0.5-1.5, the mass ratio of chitosan-zinc oxide to modifier is 100:1-40, and the mass ratio of modified chitosan-zinc oxide to the composite material as a whole is 0.5-15:100; preferably, the molar ratio of chitosan to zinc oxide is 1:0.8-1.2, the mass ratio of chitosan-zinc oxide to modifier is 100:5-25, and the mass ratio of modified chitosan-zinc oxide to acrylate monomer is 3-10:100. The amount of each component in the product is controlled to ensure the antibacterial and water-resistant properties of the final product.
[0062] It should be noted that the chitosan-zinc oxide-acrylate composite material provided in the embodiment of the present invention can be further mixed with a dressing solvent to form a final wound dressing product, which can be used by a spraying method, including but not limited to spraying, spin coating, dipping, etc.
[0063] In summary, the embodiment of the present invention uses a chemical precipitation method to prepare chitosan-zinc oxide powder, and at the same time modifies it to increase its dispersibility in organic solvents, and introduces reactive double bonds to prepare modified chitosan-zinc oxide with carbon-carbon double bonds. The modified chitosan-zinc oxide is polymerized with an acrylate monomer by an in-situ polymerization method, and the resulting polymer is dissolved in a target solvent to obtain a wound dressing with good water-resistant, antibacterial and biocompatibility. Compared with traditional wound dressings, the water resistance has been significantly improved, and the antibacterial performance and biocompatibility have also been significantly improved, and there is no significant effect on other properties of the wound dressing, and the process is simple and easy, the cost is lower, and it is suitable for large-scale production.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1
[0066] This embodiment provides a method for preparing a chitosan-zinc oxide-acrylate composite material, comprising the following steps:
[0067] (1) Preparation of chitosan-zinc oxide powder
[0068] Add 150mL of deionized water and 720μL of glacial acetic acid to a 250mL beaker. After stirring evenly, weigh 0.5g of chitosan and pour it into the acetic acid aqueous solution, stirring for about 15min until the chitosan is completely dissolved. Weigh 1g of zinc acetate dihydrate, and after the zinc acetate is completely dissolved, transfer the beaker to a heat-collecting constant-temperature magnetic stirrer for constant-temperature stirring at a stirring rate of 200r / min. After the temperature rises to 60°C, add 1mol / L of sodium hydroxide aqueous solution dropwise to adjust the solution pH to 10, keep the temperature and speed unchanged, and the reaction ends after 4h of reaction.
[0069] After the reaction is completed, the reaction product is poured into a 100 mL centrifuge tube and washed alternately with deionized water and anhydrous ethanol until the pH of the reaction product mixture is neutral. After centrifugal washing, the mixture is placed in a vacuum drying oven at 60° C. for 12 h.
[0070] (2) Modification of chitosan-zinc oxide
[0071] Weigh 2g chitosan-zinc oxide and measure 120mL anhydrous ethanol and 20mL deionized water, and pour the above raw materials into a 250mL three-necked flask. Stir magnetically at 1000r / min for 30min, then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min. After the ultrasound is completed, transfer the flask to a heat-collecting magnetic stirrer for constant temperature stirring at 200r / min. When the temperature rises to 80°C, use a pipette to draw γ-methacryloxypropyltrimethoxysilane and add it. The mass ratio of γ-methacryloxypropyltrimethoxysilane to the total mass of chitosan-zinc oxide is 20:100, and stir in a constant temperature 80°C oil bath for 2h. After stirring, pour the mixed solution in the flask into a 100mL centrifuge tube, centrifuge at 8000r / min for 2min, and use anhydrous ethanol and ultrapure water to alternately centrifuge and wash 3 times, and the centrifugal speed and time remain unchanged. After washing, dry in a vacuum oven at 80°C for 8 hours. After drying, grind thoroughly with a mortar and store in a well-sealed reagent bottle for later use.
[0072] (3) Preparation of chitosan-zinc oxide-acrylate composites
[0073] Accurately weigh 20g of methyl methacrylate, 3g of lauryl methacrylate, and 6g of butyl acrylate, and store them in a sealed 50mL beaker. Take a three-necked flask, add 50mL of cyclohexane to it, pour the measured solvent into a 250mL three-necked flask, weigh 1% of the total mass of the acrylate monomer modified chitosan-zinc oxide and add it, stir magnetically at 1000r / min for 30min, then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min, so that the modified powder is evenly dispersed in cyclohexane. After the ultrasound is finished, transfer the flask to a heat-collecting constant temperature magnetic stirrer, and pour the three monomers weighed in turn, raise the temperature to 80℃ and stir at a constant temperature, ensure that the oil level in the stirrer is higher than the liquid level in the three-necked flask by (1-2)cm, and adjust the stirrer speed to 180r / min. Weigh 1.5% benzoyl peroxide to the total mass of the monomer and modified chitosan-zinc oxide, weigh 2 / 3 and 1 / 3 of the mass separately and save. When the temperature in the three-necked flask reaches 80°C, add 2 / 3 benzoyl peroxide. After 2 hours, add 1 / 3 benzoyl peroxide. Keep the stirrer speed unchanged and react for 6 hours.
[0074] (4) Preparation of wound dressings
[0075] The composite polymer obtained in step (3) was washed with water and ethanol, and then vacuum dried for 6 hours to obtain a pure composite polymer. 1.4 g of the composite polymer was weighed and dissolved in 30 mL of cyclohexane to prepare a wound dressing solution.
[0076] Example 2
[0077] This embodiment provides a method for preparing a chitosan-zinc oxide-acrylate composite material, comprising the following steps:
[0078] (1) Preparation of chitosan-zinc oxide powder
[0079] Add 120mL of deionized water and 920μL of glacial acetic acid to a 250mL beaker. After stirring evenly, weigh 0.4g of chitosan and pour it into the acetic acid aqueous solution, stirring for about 15min until the chitosan is completely dissolved. Weigh 1.2g of zinc acetate dihydrate, and after the zinc acetate is completely dissolved, transfer the beaker to a heat-collecting constant-temperature magnetic stirrer for constant-temperature stirring at a stirring rate of 200r / min. After the temperature rises to 70°C, add 3mol / L of sodium hydroxide aqueous solution dropwise to adjust the solution pH to 11, keep the temperature and speed unchanged, and the reaction ends after 5h of reaction.
[0080] After the reaction is completed, the reaction product is poured into a 100 mL centrifuge tube and washed alternately with deionized water and anhydrous ethanol until the pH of the reaction product mixture is neutral. After centrifugal washing, the mixture is placed in a vacuum drying oven at 60° C. for 12 h.
[0081] (2) Modification of chitosan-zinc oxide
[0082] Weigh 2g chitosan-zinc oxide and measure 100mL anhydrous ethanol and 30mL deionized water, and pour the above raw materials into a 250mL three-necked flask. Stir magnetically at 1000r / min for 30min, and then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min. After the ultrasound is completed, transfer the flask to a heat-collecting magnetic stirrer and stir at a constant temperature of 200r / min. When the temperature rises to 70°C, use a pipette to draw γ-methacryloxypropyltrimethoxysilane and add it. The ratio of the mass of γ-methacryloxypropyltrimethoxysilane to the total mass of chitosan-zinc oxide is 15:100, and stir in a constant temperature 70°C oil bath for 2h. After stirring, pour the mixed solution in the flask into a 100mL centrifuge tube, centrifuge at 8000r / min for 2min, and use anhydrous ethanol and ultrapure water to alternately centrifuge and wash 3 times, and the centrifugal speed and time remain unchanged. After washing, dry in a vacuum oven at 80°C for 8 hours. After drying, grind thoroughly with a mortar and store in a well-sealed reagent bottle for later use.
[0083] (3) Preparation of chitosan-zinc oxide-acrylate composites
[0084] Accurately weigh 22g of methyl methacrylate, 3g of lauryl methacrylate, and 4g of butyl acrylate, and store them in a sealed 50mL beaker. Take a three-necked flask, add 50mL of cyclohexane to it, pour the measured solvent into a 250mL three-necked flask, weigh 2% of the total mass of the acrylate monomer modified chitosan-zinc oxide and add it, stir magnetically at 1000r / min for 30min, then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min, so that the modified powder is evenly dispersed in cyclohexane. After the ultrasound is finished, transfer the flask to a heat-collecting constant temperature magnetic stirrer, and pour the three monomers weighed in turn, raise the temperature to 70℃ and stir at a constant temperature, ensure that the oil level in the stirrer is higher than the liquid level in the three-necked flask by (1-2)cm, and adjust the stirrer speed to 180r / min. Weigh 1% benzoyl peroxide accounting for the total weight of the monomer and the modified chitosan-zinc oxide, weigh and store 2 / 3 and 1 / 3 of the weight separately. When the temperature in the three-necked flask reaches 70°C, add 2 / 3 benzoyl peroxide. After 2 hours, add 1 / 3 benzoyl peroxide. Keep the stirrer speed unchanged and react for 7 hours.
[0085] (4) Preparation of wound dressings
[0086] The composite polymer obtained in step (3) was washed with water and ethanol, and then vacuum dried for 6 hours to obtain a pure composite polymer. 1.2 g of the composite polymer was weighed and dissolved in 30 mL of cyclohexane to prepare a wound dressing solution.
[0087] Example 3
[0088] This embodiment provides a method for preparing a chitosan-zinc oxide-acrylate composite material, comprising the following steps:
[0089] (1) Preparation of chitosan-zinc oxide powder
[0090] Add 150mL of deionized water and 800μL of glacial acetic acid to a 250mL beaker. After stirring evenly, weigh 0.5g of chitosan and pour it into the acetic acid aqueous solution, stirring for about 15min until the chitosan is completely dissolved. Weigh 1.2g of zinc acetate dihydrate, and after the zinc acetate is completely dissolved, transfer the beaker to a heat-collecting constant-temperature magnetic stirrer for constant-temperature stirring at a stirring rate of 200r / min. After the temperature rises to 80°C, add 2mol / L of sodium hydroxide aqueous solution dropwise to adjust the solution pH to 9, keep the temperature and speed unchanged, and the reaction ends after 3h of reaction.
[0091] After the reaction is completed, the reaction product is poured into a 100 mL centrifuge tube and washed alternately with deionized water and anhydrous ethanol until the pH of the reaction product mixture is neutral. After centrifugal washing, the mixture is placed in a vacuum drying oven at 60° C. for 12 h.
[0092] (2) Modification of chitosan-zinc oxide
[0093] Weigh 2g chitosan-zinc oxide and measure 150mL anhydrous ethanol and 10mL deionized water, and pour the above raw materials into a 250mL three-necked flask. Stir magnetically at 1000r / min for 30min, and then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min. After the ultrasound is completed, transfer the flask to a heat-collecting magnetic stirrer and stir at a constant temperature of 200r / min. When the temperature rises to 75°C, use a pipette to draw vinyl trimethoxy silane and add it. The mass ratio of vinyl trimethoxy silane to the total mass of chitosan-zinc oxide is 10:100, and stir in a constant temperature 75°C oil bath for 2h. After stirring, pour the mixed solution in the flask into a 100mL centrifuge tube, centrifuge at 8000r / min for 2min, and use anhydrous ethanol and ultrapure water to alternately centrifuge and wash 3 times, and the centrifugal speed and time remain unchanged. After washing, dry it at 80°C in a vacuum drying oven for 8h. After drying, use a mortar to fully grind and store in a well-sealed reagent bottle for later use.
[0094] (3) Preparation of chitosan-zinc oxide-acrylate composites
[0095] Accurately weigh 15g of methyl methacrylate, 15g of lauryl methacrylate, and 12g of butyl acrylate, and seal them in a 50mL beaker. Take a three-necked flask, add 50mL of ethyl acetate to it, pour the measured solvent into a 250mL three-necked flask, weigh 4% of the total mass of the acrylate monomer modified chitosan-zinc oxide and add it, stir magnetically at 1000r / min for 30min, then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min, so that the modified powder is evenly dispersed in cyclohexane. After the ultrasound is finished, transfer the flask to a heat-collecting constant temperature magnetic stirrer, and pour the three monomers weighed in turn, raise the temperature to 75℃ and stir at a constant temperature, ensure that the oil level in the stirrer is higher than the liquid level in the three-necked flask by (1-2)cm, and adjust the stirrer speed to 180r / min. Weigh 2% azobisisobutylnitrile accounting for the total weight of the monomer and the modified chitosan-zinc oxide, weigh and store 2\3 and 1\3 of the weight separately. When the temperature in the three-necked flask reaches 75°C, add 2\3 azobisisobutylnitrile. After 2 hours, add 1\3 azobisisobutylnitrile. Keep the stirrer speed unchanged and react for 6 hours.
[0096] (4) Preparation of wound dressings
[0097] The composite polymer obtained in step (4) was washed with water and ethanol, and then vacuum dried for 6 hours to obtain a pure composite polymer. 1 g of the composite polymer was weighed and dissolved in 30 mL of ethyl acetate to prepare a wound dressing solution.
[0098] Example 4
[0099] This embodiment provides a method for preparing a chitosan-zinc oxide-acrylate composite material, comprising the following steps:
[0100] (1) Preparation of chitosan-zinc oxide powder
[0101] Add 150mL of deionized water and 750μL of glacial acetic acid to a 250mL beaker. After stirring evenly, weigh 0.4g of chitosan and pour it into the acetic acid aqueous solution, stirring for about 15min until the chitosan is completely dissolved. Weigh 0.9g of zinc acetate dihydrate, and after the zinc acetate is completely dissolved, transfer the beaker to a heat-collecting constant-temperature magnetic stirrer for constant-temperature stirring at a stirring rate of 200r / min. After the temperature rises to 100℃, add 4mol / L sodium hydroxide aqueous solution dropwise to adjust the solution pH to 10, keep the temperature and speed unchanged, and the reaction ends after 6h of reaction.
[0102] After the reaction is completed, the reaction product is poured into a 100 mL centrifuge tube and washed alternately with deionized water and anhydrous ethanol until the pH of the reaction product mixture is neutral. After centrifugal washing, the mixture is placed in a vacuum drying oven at 60° C. for 12 h.
[0103] (2) Modification of chitosan-zinc oxide
[0104] Weigh 2g chitosan-zinc oxide and measure 140mL anhydrous ethanol and 25mL deionized water, and pour the above raw materials into a 250mL three-necked flask. Stir magnetically at 1000r / min for 30min, and then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min. After the ultrasound is completed, transfer the flask to a heat-collecting magnetic stirrer and stir at a constant temperature of 200r / min. When the temperature rises to 80℃, use a pipette to draw vinyl triethoxysilane and add it. The mass ratio of vinyl triethoxysilane to the total mass of chitosan-zinc oxide is 25:100, and stir in a constant temperature 80℃ oil bath for 2h. After stirring, pour the mixed solution in the flask into a 100mL centrifuge tube, centrifuge at 8000r / min for 2min, and use anhydrous ethanol and ultrapure water to alternately centrifuge and wash 3 times, and the centrifugal speed and time remain unchanged. After washing, dry it in a vacuum drying oven at 80℃ for 8h. After drying, use a mortar to fully grind and store in a well-sealed reagent bottle for later use.
[0105] (3) Preparation of chitosan-zinc oxide-acrylate composites
[0106] Accurately weigh 13g of methyl methacrylate, 13g of lauryl methacrylate, and 11g of butyl acrylate, and seal them in a 50mL beaker. Take a three-necked flask, add 50mL of cyclohexane to it, pour the measured solvent into a 250mL three-necked flask, weigh 5% of the total mass of the acrylate monomer modified chitosan-zinc oxide and add it, stir magnetically at 1000r / min for 30min, then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min, so that the modified powder is evenly dispersed in cyclohexane. After the ultrasound is finished, transfer the flask to a heat-collecting constant temperature magnetic stirrer, and pour the three monomers weighed in turn, raise the temperature to 75℃ and stir at a constant temperature, ensure that the oil level in the stirrer is higher than the liquid level in the three-necked flask by (1-2)cm, and adjust the stirrer speed to 180r / min. Weigh 1% benzoyl peroxide accounting for the total weight of the monomer and the modified chitosan-zinc oxide, and weigh and store 2 / 3 and 1 / 3 of their weight separately. When the temperature in the three-necked flask reaches 75°C, add 2 / 3 benzoyl peroxide. After 2 hours, add 1 / 3 benzoyl peroxide. Keep the stirrer speed unchanged and react for 7 hours.
[0107] (4) Preparation of wound dressings
[0108] The composite polymer obtained in step (3) was washed with water and ethanol, and then vacuum dried for 6 hours to obtain a pure composite polymer. 1.6 g of the composite polymer was weighed and dissolved in 30 mL of cyclohexane to prepare a wound dressing solution.
[0109] Example 5
[0110] This embodiment provides a method for preparing a chitosan-zinc oxide-acrylate composite material, comprising the following steps:
[0111] (1) Preparation of chitosan-zinc oxide powder
[0112] Add 150mL of deionized water and 720μL of glacial acetic acid to a 250mL beaker. After stirring evenly, weigh 0.5g of chitosan and pour it into the acetic acid aqueous solution, stirring for about 15min until the chitosan is completely dissolved. Weigh 1.1g of zinc acetate dihydrate, and after the zinc acetate is completely dissolved, transfer the beaker to a heat-collecting constant-temperature magnetic stirrer for constant-temperature stirring at a stirring rate of 200r / min. After the temperature rises to 85°C, add 3mol / L of sodium hydroxide aqueous solution dropwise to adjust the solution pH to 10, keep the temperature and speed unchanged, and the reaction ends after 4h of reaction.
[0113] After the reaction is completed, the reaction product is poured into a 100 mL centrifuge tube and washed alternately with deionized water and anhydrous ethanol until the pH of the reaction product mixture is neutral. After centrifugal washing, the mixture is placed in a vacuum drying oven at 60° C. for 12 h.
[0114] (2) Modification of chitosan-zinc oxide
[0115] Weigh 2g chitosan-zinc oxide and measure 140mL anhydrous ethanol and 25mL deionized water, and pour the above raw materials into a 250mL three-necked flask. Stir magnetically at 1000r / min for 30min, and then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min. After the ultrasound is completed, transfer the flask to a heat-collecting magnetic stirrer and stir at a constant temperature of 200r / min. When the temperature rises to 80℃, use a pipette to draw vinyl triethoxysilane and add it. The mass ratio of vinyl triethoxysilane to the total mass of chitosan-zinc oxide is 20:100, and stir in a constant temperature 80℃ oil bath for 3h. After stirring, pour the mixed solution in the flask into a 100mL centrifuge tube, centrifuge at 8000r / min for 2min, and use anhydrous ethanol and ultrapure water to alternately centrifuge and wash 3 times, and the centrifugal speed and time remain unchanged. After washing, dry it at 80℃ in a vacuum drying oven for 8h. After drying, use a mortar to fully grind and store in a well-sealed reagent bottle for later use.
[0116] (3) Preparation of chitosan-zinc oxide-acrylate composites
[0117] Accurately weigh 12g of methyl methacrylate, 15g of lauryl methacrylate, and 9g of butyl acrylate, and store them in a sealed 50mL beaker. Take a three-necked flask, add 50mL of cyclohexane to it, pour the measured solvent into a 250mL three-necked flask, weigh 6% of the total mass of the acrylate monomer modified chitosan-zinc oxide and add it, stir magnetically at 1000r / min for 30min, then move the three-necked flask to an ultrasonic machine for ultrasonic dispersion for 30min, so that the modified powder is evenly dispersed in cyclohexane. After the ultrasound is finished, transfer the flask to a heat-collecting constant temperature magnetic stirrer, and pour the three monomers weighed in turn, raise the temperature to 75℃ and stir at a constant temperature, ensure that the oil level in the stirrer is higher than the liquid level in the three-necked flask by (1-2)cm, and adjust the stirrer speed to 180r / min. Weigh 1% benzoyl peroxide accounting for the total weight of the monomer and the modified chitosan-zinc oxide, and weigh and store 2 / 3 and 1 / 3 of their weight separately. When the temperature in the three-necked flask reaches 75°C, add 2 / 3 benzoyl peroxide. After 2 hours, add 1 / 3 benzoyl peroxide. Keep the stirrer speed unchanged and react for 7 hours.
[0118] (4) Preparation of wound dressings
[0119] The composite polymer obtained in step (3) was washed with water and ethanol, and then vacuum dried for 6 hours to obtain a pure composite polymer. 1.4 g of the composite polymer was weighed and dissolved in 30 mL of ethyl acetate to prepare a wound dressing solution.
[0120] Example 6
[0121] The only difference from Example 1 is that in step (3), the ratio of soft and hard acrylic acid monomers is 1:2.4.
[0122] Example 7
[0123] The only difference from Example 1 is that in step (3), the ratio of soft and hard acrylic acid monomers is 1:3.1.
[0124] Example 8
[0125] The only difference from Example 1 is that the reaction temperature in step (3) is controlled to be 60°C.
[0126] Example 9
[0127] The only difference from Example 1 is that the amount of benzoyl peroxide added in step (3) accounts for 0.5% of the total mass of the monomer and modified chitosan-zinc oxide.
[0128] Comparative Example 1
[0129] This comparative example provides a method for preparing a wound dressing, comprising the following steps:
[0130] (1) Synthesis of polyacrylate
[0131] Weigh 12g of methyl methacrylate, 15g of lauryl methacrylate, and 9g of butyl acrylate, and store them in a sealed 50mL beaker. Take a clean 250mL three-necked flask and use a measuring cylinder to measure 50mL of the reaction medium solvent cyclohexane. Pour the measured solvent into the 250mL three-necked flask, and pour the three monomers weighed in turn, and add a 30mm olive-shaped stirring bar. Transfer the assembled three-necked flask to a heat-collecting magnetic stirrer, and ensure that the oil level in the stirrer is (1-2)cm higher than the liquid level in the three-necked flask, and adjust the stirrer speed to 180r / min. Weigh 1% of the total mass of the monomers, and weigh and store 2 / 3 and 1 / 3 of its mass separately. When the temperature in the three-necked flask reaches 75°C, add 2 / 3 of azobisisobutylnitrile. Add 1 / 3 of azobisisobutylnitrile after 2h. Keep the stirrer speed unchanged until the reaction time reaches 7h.
[0132] (2) Preparation of wound dressings
[0133] The composite polymer obtained in step (1) was washed with water and ethanol and then vacuum dried for 6 hours to obtain a pure polymer. 1.4 g of the polymer was weighed and dissolved in 30 mL of ethyl acetate to prepare a wound dressing solution.
[0134] Comparative Example 2
[0135] The only difference from Example 5 is that the modification in step (2) is not performed, and the chitosan-zinc oxide powder obtained in step (1) is directly used for the polymerization of acrylate monomers.
[0136] Comparative Example 3
[0137] The only difference from Example 5 is that chitosan is replaced by gelatin.
[0138] Test example
[0139] (1) The materials obtained in the embodiments and comparative examples were tested for water resistance. The results are as follows Figure 1 shown.
[0140] Test method: Based on GB / T 1733-1993, a layer of blue pigment that is easily soluble in water is spin-coated between the film and the glass, and the dissolution of the blue pigment over time is observed to test the water resistance of each embodiment.
[0141] from Figure 1 It can be seen that with the increase of the content of the modified chitosan-zinc oxide participating in the reaction, the dissolution rate of the blue pigment gradually slows down, and this is due to the gradual increase in the degree of crosslinking inside the polymer, which gradually improves the water resistance of the polymer. Therefore, the polymer film is less likely to be dissolved by water, and the dissolution time of the blue pigment gradually slows down. Its water-resistant effect is overall higher than that of Comparative Example 1 to which modified chitosan-zinc oxide is not added.
[0142] (2) The antibacterial properties of the materials obtained in the examples and comparative examples were tested. The results are shown in Tables 1 and Figure 2 shown.
[0143] Test method: The antibacterial test uses the plate count method to characterize the antibacterial rate. The calculation formula is as follows:
[0144]
[0145] Among them, P is the antibacterial rate, X0 is the average colony count of the control group, and X1 is the average colony count of the experimental group.
[0146] Table 1 24h antibacterial results of each example against Escherichia coli
[0147]
[0148] From Table 1 and Figure 2It can be seen that with the increase of the content of the modified chitosan-zinc oxide participating in the reaction, the content of the antibacterial substance in the composite material increases, so the antibacterial effect on Escherichia coli gradually increases. Its antibacterial effect is higher than that of Comparative Example 1 without adding antibacterial substances, while the amount of antibacterial substance modified chitosan-zinc oxide added in Example 1 is small, the content of antibacterial substances located on the surface of the composite material is low, and the antibacterial effect is general. Compared with Example 5, Comparative Example 2 is not modified by chitosan-zinc oxide, so chitosan-zinc oxide is not bonded to the acrylate monomer in the form of a chemical bond, and its dispersion is greatly reduced, so the antibacterial substance is unevenly distributed in the composite material, resulting in a greatly reduced antibacterial performance. Compared with Example 5, Comparative Example 3 replaces chitosan with gelatin without antibacterial performance, so the antibacterial performance of the obtained composite powder is not as good as chitosan-zinc oxide, resulting in the antibacterial performance of the composite material is also reduced.
[0149] (3) The biocompatibility test of the materials obtained in the examples and comparative examples was performed. The results are as follows: Figure 3 and Figure 4 shown.
[0150] Test method: The number of live cells and dead cells after mixing with the polymers of each example was detected by cell live-dead staining experiment to determine the biocompatibility of the polymer. The effect of the polymers of each example on cell activity was detected by CCK8 to determine the biocompatibility of the polymer.
[0151] from Figure 3 and Figure 4 It can be seen that the composite material containing modified chitosan-zinc oxide has a significant promoting effect on cell activity compared with the blank group. And as the number of test days increases, its effect of promoting cell activity becomes more and more obvious. This is because zinc oxide releases zinc ions (Zn 2+ ), the growth and metabolism of many cells depend on zinc ions. Furthermore, since most zinc oxide is coated with acrylate polymer segments, the polymer has a sustained release effect on the release of zinc ions from zinc oxide in the aqueous phase, enabling it to effectively release low concentrations of zinc ions for a long time. Therefore, the chitosan-zinc oxide-acrylate composite material has a continuous promoting effect on cell activity. The composite material containing modified chitosan-zinc oxide has no obvious toxic effect on cells, and compared with the blank group, it was found that the cells were in a normal life cycle.
[0152] (4) The materials obtained in the embodiments and comparative examples were tested for moisture permeability. The results are as follows Figure 5 shown.
[0153] Test method: The water vapor permeability and water vapor permeability coefficient of the polymer film of each embodiment were tested using a W3 / 031 water vapor permeability meter to determine the moisture permeability of each embodiment.
[0154] from Figure 5 It can be seen that with the increase of the content of modified chitosan-zinc oxide participating in the reaction, the water vapor permeability of the composite film gradually decreases. This is because the increase of modified chitosan-zinc oxide content will make the film structure more compact, thereby hindering the penetration of water vapor molecules, but its value is still higher than the national standard.
[0155] (5) Solubility test was performed on Example 1, Example 6 and Example 7. The results are shown in Table 2.
[0156] Table 2 shows the solubility test results of Example 1, Example 6 and Example 7.
[0157] Cyclohexane Ethyl acetate Isooctane Example 1 Soluble Soluble Refractory Example 6 Slightly soluble Soluble Poorly soluble Example 7 Poorly soluble Slightly soluble Very insoluble
[0158] It can be seen from Table 2 that as the proportion of hard monomer increases, the polarity of the composite material increases and the solubility in the dressing solvent gradually decreases.
[0159] (6) The reaction degree of Example 1 and Examples 8 and 9 was tested. The results are shown in Table 3.
[0160] Table 3 is the comparison results of the reaction degree of Example 1, Example 8 and Example 9
[0161] Example Conversion rate Example 1 93.28% Example 8 75.14% Example 9 80.97%
[0162] As can be seen from Table 3, the degree of reaction is characterized by the conversion rate. Compared with Example 1, the reaction temperature of Example 8 is reduced, resulting in a decrease in the reaction rate, so the degree of reaction is reduced. Compared with Example 1, the content of the added initiator of Example 9 is reduced, and the concentration of active free radicals contained in the reaction solution system is reduced, resulting in a lower reaction rate in the chain growth stage, so the degree of reaction is reduced.
[0163] In summary, the chitosan-zinc oxide-acrylate composite material prepared by the present invention has an optimal ratio of acrylate soft and hard monomers of 7:13 through experimental testing, and the addition amount of zinc oxide is 6%. The antibacterial rate is more than 99%, because chitosan-zinc oxide has a strong antibacterial effect, which makes the polyacrylate, which does not have antibacterial properties, have antibacterial ability. Compared with traditional wound dressings, it has the following advantages:
[0164] (1) Excellent water resistance
[0165] This is because zinc oxide plays a cross-linking role in the polymer matrix, making the various parts of the polymer more continuous and the structural density greatly improved, resulting in reduced permeability of the film to water and improved water resistance.
[0166] (2) Excellent biocompatibility
[0167] Its biocompatibility is also greatly improved compared with traditional wound dressings, because zinc oxide releases zinc ions (Zn 2+ ), the growth and metabolism of many cells depend on zinc ions. Furthermore, since most of the zinc oxide is coated with acrylate polymer segments, the polymer has a sustained release effect on the release of zinc ions from zinc oxide in the aqueous phase, enabling it to effectively release low concentrations of zinc ions for a long time. At the same time, the addition of chitosan will also improve the biocompatibility of the composite material. Therefore, the chitosan-zinc oxide-acrylate composite material prepared in the laboratory has a continuous promoting effect on cell activity, thereby making it have good biocompatibility.
[0168] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A chitosan-zinc oxide-acrylate composite material, characterized in that: The modified chitosan-zinc oxide is obtained by polymerizing a modified chitosan-zinc oxide and an acrylate monomer, wherein the modifier used in the preparation process of the modified chitosan-zinc oxide is at least one selected from γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane; The preparation process of the modified chitosan-zinc oxide comprises: mixing chitosan-zinc oxide powder with a first solvent and the modifier, reacting at 50° C. to 100° C. for 1 h to 8 h; The preparation process of the chitosan-zinc oxide powder comprises: mixing chitosan and a zinc source in an acidic solution, then adjusting the pH value to 8-11 with an alkaline solution, reacting at 60° C.-100° C. for 2h-6h to obtain a suspension, and sequentially performing solid-liquid separation, washing and drying on the suspension.
2. The chitosan-zinc oxide-acrylate composite material according to claim 1, characterized in that: The molar ratio of chitosan to zinc oxide is 1:0.5-1.5, the mass ratio of chitosan-zinc oxide to modifier is 100:1-40, and the mass ratio of modified chitosan-zinc oxide to acrylate monomer is 0.5-15:
100.
3. The chitosan-zinc oxide-acrylate composite material according to claim 2, characterized in that: The molar ratio of chitosan to zinc oxide is 1:0.8-1.2, the mass ratio of the total mass of chitosan and zinc oxide to the modifier is 100:5-25, and the mass ratio of modified chitosan-zinc oxide to acrylate monomer is 3-10:
100.
4. A method for preparing the chitosan-zinc oxide-acrylate composite material according to any one of claims 1 to 3, characterized in that: include: preparing the modified chitosan-zinc oxide, and then polymerizing the modified chitosan-zinc oxide and the acrylate monomer; The preparation process of the modified chitosan-zinc oxide comprises: mixing chitosan-zinc oxide powder with a first solvent and the modifier, reacting at 50° C. to 100° C. for 1 h to 8 h; The preparation process of the chitosan-zinc oxide powder comprises: mixing chitosan and a zinc source in an acidic solution, then adjusting the pH value to 8-11 with an alkaline solution, reacting at 60° C.-100° C. for 2h-6h to obtain a suspension, and sequentially performing solid-liquid separation, washing and drying on the suspension.
5. The preparation method according to claim 4, characterized in that: The first solvent is selected from at least one of methanol, ethanol, water and isopropanol.
6. The preparation method according to claim 4, characterized in that: After the reaction with the modifier is completed, solid-liquid separation, washing and drying are carried out in sequence.
7. The preparation method according to claim 4, characterized in that: The chitosan is first mixed with the acidic solution and then mixed with the zinc source.
8. The preparation method according to claim 7, characterized in that: The zinc source is selected from at least one of zinc acetate dihydrate and zinc nitrate hexahydrate.
9. The preparation method according to claim 7, characterized in that: The acidic solution is selected from at least one of an acetic acid solution and an oxalic acid solution.
10. The preparation method according to claim 4, characterized in that: The alkali solution is selected from at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkali solution is 1 mol / L to 5 mol / L.
11. The preparation method according to claim 4, characterized in that: The process of polymerizing the modified chitosan-zinc oxide and the acrylate monomer comprises: mixing the modified chitosan-zinc oxide, the acrylate monomer and a second solvent, and performing a polymerization reaction in the presence of an initiator.
12. The preparation method according to claim 11, characterized in that: The polymerization reaction temperature is 40°C to 100°C, and the polymerization reaction time is 2h to 10h.
13. The preparation method according to claim 11, characterized in that: Also includes: Washing and drying are carried out after the polymerization is completed.
14. The preparation method according to claim 13, characterized in that: The washing is performed by using water and alcohol solvents for multiple washings.
15. The preparation method according to claim 11, characterized in that: The mass ratio of the modified chitosan-zinc oxide to the acrylate monomer is 0.5-15:
100.
16. The preparation method according to claim 11, characterized in that: The second solvent is selected from at least one of cyclohexane, isooctane and toluene.
17. The preparation method according to claim 11, characterized in that: The initiator is selected from at least one of benzoyl peroxide and azobisisobutylnitrile, and the mass ratio of the initiator to the acrylate monomer is 0.1 to 2:
100.
18. The preparation method according to claim 11, characterized in that: The acrylic acid ester monomer is selected from at least one of methyl methacrylate, lauryl methacrylate, butyl acrylate and isooctyl acrylate.
19. The preparation method according to claim 18, characterized in that: The acrylate monomers include acrylate soft monomers and acrylate hard monomers, and the mass ratio of the acrylate soft monomers to the acrylate hard monomers is 1:1.7-4.5; the acrylate soft monomers are selected from at least one of lauryl methacrylate, butyl acrylate and isooctyl acrylate, and the acrylate hard monomers are selected from at least one of methyl methacrylate, methyl acrylate and isobornyl acrylate.
20. Use of the chitosan-zinc oxide-acrylate composite material according to any one of claims 1 to 3 or the chitosan-zinc oxide-acrylate composite material prepared by the preparation method according to any one of claims 4 to 19 in preparing wound dressings.
21. The use according to claim 20, characterized in that The preparation process of the wound dressing comprises: mixing the chitosan-zinc oxide-acrylate composite material with a dressing solvent.
Citation Information
Patent Citations
Preparation method of modified chitosan-acrylate composite oil-absorptive resin
CN103289016A
Preparation method of composite film added with arginine acidified chitosan and zinc oxide nanoparticles
CN114409936A